2017
DOI: 10.1007/s10967-016-5148-z
|View full text |Cite
|
Sign up to set email alerts
|

Research with radiation and radioisotopes to better understand plant physiology and agricultural consequences of radioactive contamination from the Fukushima Daiichi nuclear accident

Abstract: Research carried out by me and my group over the last almost four decades are summarized here. The main emphasis of my work was and continues to be on plant physiology using radiation and radioisotopes. Plants live on water and inorganic elements. In the case of water, we developed neutron imaging methods and produced 15 O-labeled water (half-life 2 min) and applied them to understand water circulation pattern in the plant. In the case of elements, we developed neutron activation analysis methods to analyze a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…Fig. 4.16 32 P-phosphate distribution in a soybean plant [7]. 32 P-phosphate was supplied from the root, and the accumulation pattern of 32 P was recorded by RRIS.…”
Section: P Imaging In a Soybean Plantmentioning
confidence: 97%
See 2 more Smart Citations
“…Fig. 4.16 32 P-phosphate distribution in a soybean plant [7]. 32 P-phosphate was supplied from the root, and the accumulation pattern of 32 P was recorded by RRIS.…”
Section: P Imaging In a Soybean Plantmentioning
confidence: 97%
“…Fig. 4.18 Image analysis of the 32 P-phosphate accumulation in the pod [7]. The pseudocolor was assigned based on the counts in the pixels.…”
Section: C Imaging In a Rice Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the soil present around FDNPP and the soil in the neighboring prefectures were contaminated with approximately 100,000 MBq/km 2 and 10,000 MBq/km 2 of 137 Cs, respectively [1]. The soil surface area was the most contaminated [2]. It has been predicted that several radionuclides, such as cesium ( 137 Cs, 136 Cs, 134 Cs), strontium ( 90 Sr, 89 Sr), uranium (UO 2+ ), iodine ( 131 I), thorium ( 90 Th), barium ( 140 Ba), lanthanum ( 140 La), and tritium ( 3 H) are present.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Studying long-distance transport in plants is of high interest for the investigation of functional traits under the influence of diverse environmental factors (Van Bel, 2003 ; Jahnke et al, 2009 ). Non-invasive methods using short-lived radioisotopes have been established to detect the transport of radioactive tracer in vivo (Jahnke et al, 1998 , 2009 ; Minchin and Thorpe, 2003 ; Alexoff et al, 2011 ; Garbout et al, 2012 ; Weisenberger et al, 2013 ; Hubeau and Steppe, 2015 ; Nakanishi, 2017 ). For example, after labeling a plant with 11 CO 2 , transported 11 C can be detected and localized within the supplied plant organs from outside with positron emission tomography (PET) or scintillation detectors.…”
Section: Introductionmentioning
confidence: 99%